Unraveling legitimation strategies of Chinese Internet start-ups. Issue 2 (1st June 2015) - Song Lin, Prof. Philippe Lasserre, Prof.; Su, Xiaohua; Peng, Haidong; Zhang, Shujun; Rong, Yun
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the legitimacy needs and legitimation strategies of Internet start-ups in the context of industry dynamism. Design/methodology/approach – The purpose of this paper is to explore the legitimacy needs and legitimation strategies of Internet start-ups in the context of industry dynamism. Findings – The authors found that Internet start-ups are in great need of acquiring market and relational legitimacy at their nascent stages. Conformance to the environment is widely adopted by them as a legitimacy-enhancing strategy. There is an inverted "U" relationship between the maturity of the industry and the proactivity of any legitimation strategy in the sector. In the face of high- and low-level industry maturity, start-ups tend to employ prudent strategies to build up legitimacy. While in medium-mature industries, ventures are more likely to adopt proactive and aggressive strategies. Research limitations/implications – Due to the very nature of case methodology, this study is based on a small number of observations and it is set in the context of the Internet industry. The generalizability of its findings needs to be reinforced by further concrete studies. Practical implications – This paper suggests that industry dynamism should be taken into account carefully when implementing a choice of legitimation strategies. Originality/value – This study makes an attempt to further our understanding of how industry dynamism influences firms' choices of legitimation strategies.